Numerical study of mechanisms of abnormally viscous liquid flows - Bachurina, Maria Vladimirovna; Kazakov, Aleksey Vladimirovich; Trufanova, Natalia Mikhailovna (Computational Continuum Mechanics, 2015)
The paper presents formulation and numerical implementation of the heat and mass transfer problem in recycled polymer materials with different physical and rheological properties. Since modern production uses more and more synthetic polymeric materials and the most efficient and convenient method of processing and forming of finished products is extrusion, the necessity in solving this problem occurs quite often, for example, in the process of superimposing multilayer coatings. Three-layer coating is usually made from polymer melts, the properties of which can vary over a fairly wide range. Furthermore, the viscosity of these materials depends nonlinearly on temperature and intensity of their deformation, which greatly hampers forecasting the results of interaction of stratified flows in the regions of their concurrent motion and the geometric dimensions of the resulting coating stack. The goal of this study is to assess the geometry of the available forming tool, the stability of an interface between stratified flows and to determine experimentally the dependence of the thickness of layers of polymeric materials on some process parameters. In order to simplify the problem, actual physical processes are represented by a mathematical model, which is a system of nonlinear differential equations that admit basic conservation laws. The set of partial differential equations describes the behavior of anomalously viscous liquids in conditions of forced motion and heat. For unambiguous identification of the simulated process reaching the stationary regime, the system of equations is supplemented with boundary conditions and physical and rheological properties of the tested materials. The model takes into account natural and technological limitations and assumptions. The model is implemented using a general purpose finite element code ANSYS. To verify the efficiency of the method, its parameter convergence is evaluated, and a comparative analysis is performed for forming tool operating under constant flow rate and pressure drop. The dependence of the thickness of superimposed layers on some technological parameters of the extrusion process is represented graphically. The possibility of applying the proposed model to a system of automated control for three-layer polymeric coating forming line is demonstrated.